Cognitive Style and Academic Achievement of Physical Therapy Students, University of Phayao - พรหมศรี อรุณีย์ (Trends of Humanities and Social Sciences Research, 2019)
Cognitive style is a term used in cognitive psychology to describe the way individuals think, perceive and remember information. Cognitive style differs from cognitive ability or level, and a cognitive style test is not an intelligence test. The purpose of this study was to classify the type of cognitive styles of undergraduate physical therapy students, University of Phayao, who studied in the first semester, 2013. The 147 physical therapy students were asked to answer the questions of the cognitive style assessment. The information about cognitive styles was analyzed and classified as three types, including Dependence, Independence, and Developed-participation. The results shown that the cognitive styles of the physical therapy students were Developed-participation type (72.90%) and Independence type (27.10%), and there was no student in Dependence type. Furthermore, the cognitive styles of physical therapy student were found to be not correlated with the academic achievement, but a significant negative relationship was represented between the academic achievement and of physical therapy students’ age.